О некоторых особенностях размножения ондатры (Ondatra zibethica L.) в низовьях Днепра - Берестенников, Д.С. (Вестник зоологии, 1971)
The article deals with the results of investigation of Ondatra zibethica L. reproduction in the Low Dnieper area. The value of younger animal losses under the effect of sharp fluctuation in the water level in open and closed basins is found out. Younger animal yield per adult female in open basins is 4.3, in closed ones—12.5 individuals Reproduction of Ondatra zibethica in the Low Dnieper area ends in September. The 2-, 3-years old females are the most fecund. An average number of postembrionic spots is 16.2, maximum one — 32, minimum one — 3. By the beginning of hunting 4.3 young animals or 26% on the average remain out of 16 produced by the female for the reproduction period. The main reason of low productivity of Ondatra zibethica in the low Dnieper area is an unstable water level in basins.